The Influence of Soaking Time and KNO3 Concentration On The vigor indeks of Rice Variety of Cisokan Kuniang (Oryza sativa L.) Expired - Al Adawiyah; Violita Violita; Azwir Anhar; Irma Leilani Eka Putri (Jurnal Serambi Biologi, 2022)
The germination process of expired rice seeds is quite difficult because the seeds have decreased in quality due to expiration. Rice seeds (Oryza sativa L.) expired require increased viability to increase their germination. One way to increase seed viability is to use an invigoration material in the form of KNO3 by adjusting the soaking time and the concentration of KNO3 used. This study aimed to determine the best soaking time and KNO3 concentration to increase the viability of expired rice seeds. This research was conducted at the Biology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University in May-June 2022. This study used a completely randomized design (CRD) with two treatment factors. The first factor is the length of immersion with 3 levels, namely 12 hours, 24 hours, and 48 hours. The second factor is the concentration of KNO3 with 5 levels, namely 0%, 1.5%, 2%, 2.5%, and 3%. Each treatment combination consisted of 4 replications. The parameter observed is the vigor index. The results showed that the treatment of KNO3 concentration had a significant effect on the parameters of the vigor index of expired Cisokan kuniang rice varieties. The immersion time had no significant effect on the vigor index parameter. The interaction between immersion time and KNO3 concentration significantly affected the vigor index parameter.